From “Experiencers” to “Souvenir buyers”: Segmenting Serbian tourists based on motivations for purchasing local liqueurs while travelling - Marijana Seočanac; Sonja Veljović; Marija Kostić; Katarína Hrobňová (Mенаџмент у хотелијерству и туризму, 2025)
Purpose – The main purpose of this paper is to investigate the motivations of Serbian tourists to buy authentic local liqueurs while travelling. By analysing various intrinsic and extrinsic factors that influence these purchasing decisions, the study also attempts to identify different segments of tourists with different motivations for buying liqueurs. Methodology – Data from a sample of 133 buyers were analysed using hierarchical and k-means cluster analysis. Discriminant analysis was used to validate the classification, while ANOVA was used to confirm significant differences between the clusters. Pearson’s chi-square test was used to compare the clusters on different characteristics, and descriptive statistical analysis was used to describe each cluster. Results – Three distinct segments of buyers were discovered based on their motivations for purchasing local liqueurs while travelling, namely “Experiencers”, “Aesthetes” and “Souvenir buyers”. Each segment is presented in terms of key motivating factors, liqueur purchase and demographic characteristics. Implications – The findings of this study provide valuable insights for liqueur producers and sellers, enabling them to develop targeted marketing strategies tailored to specific customer segments. Furthermore, this study represents an important step in bringing liqueurs into the wider academic discussion within tourism research, highlighting their potential to enrich tourists’ cultural experiences and increase the destination’s attractiveness.